2021
DOI: 10.3390/ma14040841
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanocomposite Implants for Interstitial Thermotherapy: Experimental and Computational Analysis

Abstract: The ferromagnetic implant (thermoseeds) technique offers desirable features for interstitial thermotherapy. However, its efficacy has been reported to be limited by issues that are related to the properties of the metal alloys that are used to fabricate them and the high number of thermoseeds needed to achieve therapeutic temperature levels. Here, we present the results of a combination of experimental and computational analysis of plasmonic nanocomposite implants (photoseeds)—a combination of Au nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The type of laser applied in many photothermal investigations was near infrared, with wavelength spectra of 785 nm up to 1046 nm, with 808 nm wavelength used more frequently, according to a review by Fekrazad et al 76 Hence, the 808 nm wavelength was the most effective in prior studies [77][78][79] of the photothermal destruction of cancer cells. 76 In addition, the current results suggest that the magnetitereinforced PDMS nanocomposites reinforced with 5% weight percentage of MNPs exhibit the best heating characteristics for controlled laser-induced hyperthermia at depths up to 8 mm below the surface, when the power of the incident laser is 0.6 W. However, for laser power above 0.6 W, the current work also suggests that the higher temperatures that result from laser illumination at higher incident powers (above 0.6 W).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of laser applied in many photothermal investigations was near infrared, with wavelength spectra of 785 nm up to 1046 nm, with 808 nm wavelength used more frequently, according to a review by Fekrazad et al 76 Hence, the 808 nm wavelength was the most effective in prior studies [77][78][79] of the photothermal destruction of cancer cells. 76 In addition, the current results suggest that the magnetitereinforced PDMS nanocomposites reinforced with 5% weight percentage of MNPs exhibit the best heating characteristics for controlled laser-induced hyperthermia at depths up to 8 mm below the surface, when the power of the incident laser is 0.6 W. However, for laser power above 0.6 W, the current work also suggests that the higher temperatures that result from laser illumination at higher incident powers (above 0.6 W).…”
Section: Discussionmentioning
confidence: 99%
“…The type of laser applied in many photothermal investigations was near infrared, with wavelength spectra of 785 nm up to 1046 nm, with 808 nm wavelength used more frequently, according to a review by Fekrazad et al 76 Hence, the 808 nm wavelength was the most effective in prior studies 77–79 of the photothermal destruction of cancer cells 76 …”
Section: Discussionmentioning
confidence: 99%
“…31 It has also been reported that iron oxide nanoparticles are more widely used than other magnetic nanoparticles due to their biocompatibility and chemical inertness that make them suitable for medical, pharmaceutical and therapeutic applications. 16,32,33 Also magnetite/PDMS nanocomposites are biocompatible, inert and nontoxic, 34 making them excellent candidates for applications in biomedical devices for breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%